2019
DOI: 10.3390/molecules25010097
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Model of Indeno[1,2-b]indole Derivatives and Identification of N-isopentyl-2-methyl-4,9-dioxo-4,9-Dihydronaphtho[2,3-b]furan-3-carboxamide as a Potent CK2 Inhibitor

Abstract: Casein kinase II (CK2) is an intensively studied enzyme, involved in different diseases, cancer in particular. Different scaffolds were used to develop inhibitors of this enzyme. Here, we report on the synthesis and biological evaluation of twenty phenolic, ketonic, and para-quinonic indeno[1,2-b]indole derivatives as CK2 inhibitors. The most active compounds were 5-isopropyl-1-methyl-5,6,7,8-tetrahydroindeno[1,2-b]indole-9,10-dione 4h and 1,3-dibromo-5-isopropyl-5,6,7,8-tetrahydroindeno[1,2-b]indole-9,10-dion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Furan-3-carboxamide derivatives are basic units of many natural products. [65][66][67] They possess diverse biological applications like usage in treatment of antiviral infections and hyperproliferative diseases. 68 In 2014, Yong Rok Lee et al reported a regioselective synthesis of furan-3-carboxamide derivatives using cascade formal [3+2] cycloaddition (Scheme 21).…”
Section: Account Synlettmentioning
confidence: 99%
“…Furan-3-carboxamide derivatives are basic units of many natural products. [65][66][67] They possess diverse biological applications like usage in treatment of antiviral infections and hyperproliferative diseases. 68 In 2014, Yong Rok Lee et al reported a regioselective synthesis of furan-3-carboxamide derivatives using cascade formal [3+2] cycloaddition (Scheme 21).…”
Section: Account Synlettmentioning
confidence: 99%
“…Naphthofurans fused or coupled with oxygen and nitrogen heterocycles do not occur in nature. Even synthetic naphthofurans coupled or fused with oxygen and nitrogen heterocycle are not reported so far, except for some reports of such compounds from this literature method [73][74][75][76][77][78]. These observations prompted us to undertake the investigation of naphthofuran with oxadiazole and indole as second heterocyclic components.…”
Section: Biologically Active Naphthofuransmentioning
confidence: 99%
“…All chemicals were purchased in the highest purity available. The four tetrahydroindeno [1,2-b]indole-9,10-diones 5a,b were synthesized according to previously reported methods [38,40,41] (detailed description of the synthetic pathway can be found in Supporting Information; Scheme S1). Compounds 5a,b and CX-4945 were dissolved at a concentration of 10 mM in dimethyl sulfoxide (DMSO).…”
Section: Chemical Synthesismentioning
confidence: 99%